Distribution of Drimane Sesquiterpenoids and Tocopherols in Liverworts, Ferns and Higher Plants: Polygonaceae, Canellaceae and Winteraceae Species - Asakawa,Yoshinori (2012)
The liverwort, Porella vernicosa complex produces a very hot tasting polygodial, a drimane-type sesquiterpene dialdehyde. The same compound has been isolated from two ferns, Thelypteris hispidula and Blechnum fluviatile, as well as from the higher plants Polygonum hydropiper, P. hydropiper f. purpurascens (Polygonaceae), Cinnamosma, Caspicodendron, Canella and Warburgia species (Canellaceae), and Pseudowintera colorata, Tasmannia lanceolata, Drimys and Zygogynum species (Winteraceae). In addition, the liverworts and higher plants which elaborate polygodial and its related pungent drimane dials contain a small amount of alpha-tocopherol, gamma-tocopherol or deltha-tocotrienol. The present paper gives the results of a comparative study on the drimane-type sesquiterpenoids in some liverworts, ferns and higher plants, and the role of tocopherols in these plant groups.